Seasonal Fish Diversity And Distribution In The Manapadu Coastal Zone Of The Gulf Of Mannar, India - Nirmala, S.; Devipriya, S.; Jeyapraba, L.; Addline, D. (Journal of Neonatal Surgery, 2025)
This study assessed the diversity and distribution of fish fauna in the Manapadu coastal zone of the Gulf of Mannar, Tamil Nadu, India. A total of 110 species representing 31 families and 22 orders were documented through systematic surveys conducted during the study period.. Dominant families included Carangidae, Lutjanidae, Serranidae, Dasyatidae, and Scaridae. Biodiversity indices such as Fisher’s Alpha and Margalef richness peaked during April and November, indicating clear seasonal richness patterns, while evenness remained low due to dominance by a few species. These temporal trends likely reflect ecological processes such as breeding migrations and environmental variability affecting species assemblages. The findings highlight high species richness but skewed community structure in this biologically significant marine region. Understanding these patterns can inform local fisheries management, conservation planning, and policy decisions regarding sustainable harvest and trade. The results provide a robust baseline for future monitoring, ecological assessments, and ecosystem-based management in the Gulf of Mannar coastal ecosystem